Tibiotalocalcaneal nailing in ankle arthrodesis (Annals of Medical Research, 2021)
Aim: Our objective in this study was to present the results of the patients who had retrograde tibiotalocalcaneal implants for different etiological causes. Ankle and forefoot deformities and traumatic osteoarthritis are important problems affecting the quality of life of patients. Many implants have been tried to prevent and fix these deformities. Tibiotalocalcaneal arthrodesis with retrograde intramedullary nail is one of these implants. While there are many studies in the literature on other systems, the low number of studies on intramedullary implants and low number of patients in this patient group encouraged us to undertake this study using the available data. Material and Methods: Twelve patients who had intramedullary tibiotalocalcaneal nail installation between January 2009 and May 2013 were retrospectively evaluated. In their etiologies, 33.33% of the patients (n=4) had firearm-related injuries, 33.33% had (n=4) trauma-related arthrosis, 16.67% had (n=2) diabetic neuropathy, and 16.67% had rheumatoid arthritis. Patients were evaluated based on pre- and post-operative American Orthopedic Foot and Ankle (AOFAS) scores.Results: Union was observed in all patients. The average union duration was found at 65.8 (45–124) days. Two of the patients who had arthrodesis due to firearm injuries had deep infections, and one had a superficial infection. No complications other than infections were observed. The average AOFAS pre- and post-operative scores were 48.7 (31–80) and 68.5 (40–96).Conclusion: As a result, ankle arthrodesis with intramedullary nail is a useful and efficient method for patients with severe underlying arthritis and can produce good results.
Keywords: Ankle arthrodesis; intramedullary nail; subtalar joint; tibiotalar joint